Clinical Characteristics of Multiple Café-Au-Lait Macules and Their Potential Significance in the Early Screening of Genetic Diseases - Chen T; Wu J; Yang X; Xia Z; Yang R (Clinical, Cosmetic and Investigational Dermatology)
Tong Chen,1– 3 Jiamin Wu,1 Xin Yang,2 Zhikuan Xia,1,2 Rongya Yang1,2 1The Second School of Clinical Medicine, Southern Medical University, Guangzhou, Guangdong, 510515, People’s Republic of China; 2Department of Dermatology, The Seventh Medical Center of Chinese PLA General Hospital, Beijing, 100080, People’s Republic of China; 3Department of Dermatology, Longgang Central Hospital, Shenzhen, Guangdong, 518116, People’s Republic of ChinaCorrespondence: Rongya Yang, Email drYangRongya@outlook.com; yangrya@sina.com Zhikuan Xia, Email drXiaZhikuan@outlook.com; sum7@sina.comBackground: Café-au-lait macules (CALMs) are common skin manifestations, and their number and distribution may indicate potential genetic disorders, such as Neurofibromatosis Type 1 (NF1). This study aimed to investigate the clinical characteristics of multiple CALMs and their significance in the early screening of genetic disorders.Methods: This retrospective study included 98 patients diagnosed between May 2021 and May 2024 in two hospitals. Patients were divided into three groups based on the number of CALMs and whether other skin manifestations were present: Group 1 (≥ 6 CALMs with other skin manifestations), Group 2 (≥ 6 CALMs without other skin manifestations), and Group 3 (< 6 CALMs without other skin manifestations). Detailed clinical evaluations and imaging examinations were conducted to record the number, size, distribution of CALMs, and associated symptoms. Multivariate logistic regression analysis was performed to explore the relationship between CALMs and other systemic symptoms.Results: Group 1 patients showed significantly higher incidences of neurological symptoms (eg, neurofibromas 54%, P < 0.001) and skeletal system symptoms (eg, bone deformities 38%, P = 0.001) compared to Groups 2 and 3. Imaging examinations revealed an abnormality rate of 90% in Group 1 (P < 0.001). Logistic regression analysis indicated that the number of CALMs (≥ 10) was significantly associated with neurological (OR = 7.664, P = 0.001) and skeletal system symptoms (OR = 4.623, P = 0.014). The distribution of CALMs on the face and neck also showed a certain influence on symptoms.Conclusion: The number and distribution of CALMs are significant in the early screening of genetic diseases, particularly in identifying patients with potential neurological and skeletal system abnormalities.Keywords: café-au-lait macules, neurofibromatosis type 1, genetic disorders, early screening